The Development to Problem Solving Ability in Mathematics through the Constructivist Theory with Open Approach of Mathayomsuksa 3 Students - Somboon, Natthaleeya; Thongkamsuk, Penporn; Srihamee , Supaporn; Iamsa-ard, Areewan (Suan Dusit Graduate School Academic Journal, 2023)
The purposes of this research were to 1) compare mathematic problem - solving ability before and after learning through the constructivist theory with open approach of Mathayomsuksa 3 students and 2) study students’ satisfaction towards learning through the constructivist theory with open approach. The sample included 35 Mathayomsuksa 3/10 students from Bangmodwittaya School in the second semester of the academic year 2022 who were obtained through cluster random sampling. The research instruments involved 1) five lesson plans with the IOC 1.00 2) test of mathematic problem - solving ability with the difficulty index ranging from 0.41 to 0.68, the discrimination index ranging from 0.27 to 0.57, the validity index ranging from 0.70 to 1.00 and the reliability index at 0.91 and 3) a set of questionnaires on students’ satisfaction. Data were statistically analyzed by mean, standard deviation, and t-test for one group sample. The findings were revealed that 1) the mathematic problem-solving ability through the constructivist theory with open approach of Mathayomsuksa 3 students after the experiment was higher than that before the experiment at the significance level of .01. and 2) the students’ satisfaction towards learning activities through the constructivist theory with open approach was generally found at the ‘Highest’ level. When considering each aspect, the benefit was found at the highest level, followed by the instruction media and learning activity, respectively.